1997
DOI: 10.1093/jn/127.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss is Greater with Consumption of Large Morning Meals and Fat-Free Mass Is Preserved with Large Evening Meals in Women on a Controlled Weight Reduction Regimen ,

Abstract: The purpose of this study was to determine whether meal ingestion pattern [large morning meals (AM) vs. large evening meals (PM)] affects changes in body weight, body composition or energy utilization during weight loss. Ten women completed a metabolic ward study of 3-wk weight stabilization followed by 12 wk of weight loss with a moderately energy restricted diet [mean energy intake +/- SD = 107 +/- 6 kJ/(kg.d)] and regular exercise. The weight loss phase was divided into two 6-wk periods. During period 1, 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 18 publications
0
77
0
2
Order By: Relevance
“…These findings concur with those of others and provide limited support for the view that BMI is adversely affected by poor sleep hygiene and eating habits. 32,46 These results can provide a rationale for devising simple intervention measures aimed at preventing a rise in BMI and improving long-term health but they also show that any such advice is not being acted upon as seriously as it might be, at least with regard to medical students in Poland. Clearly, the results of the present study do not say if similar problems exist in other sections of the community in Poland, and whether the situation is similar in other countries.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These findings concur with those of others and provide limited support for the view that BMI is adversely affected by poor sleep hygiene and eating habits. 32,46 These results can provide a rationale for devising simple intervention measures aimed at preventing a rise in BMI and improving long-term health but they also show that any such advice is not being acted upon as seriously as it might be, at least with regard to medical students in Poland. Clearly, the results of the present study do not say if similar problems exist in other sections of the community in Poland, and whether the situation is similar in other countries.…”
Section: Discussionmentioning
confidence: 92%
“…The results indicate that a single meal taken in the morning is associated with a better control of body mass than the same meal taken later in the day. 32 The detailed metabolic consequences of eating the same food at different times of day have still to be established, but possible differences include the amount of physical work performed during the daytime (less if there is no food intake until the evening) and endocrine responses to food intake (the insulin response to food intake being time-of-day dependent). 33 Nevertheless, in the present study, BMI was not independently predicted by the frequency with which particular meals were eaten (with the possible exception of a marginal effect of the frequency of eating lunch), nor by the total number of meals eaten per day.…”
Section: Food Intakementioning
confidence: 99%
“…Adults who consumed breakfast regularly have significantly lower fat and cholesterol intakes [17] and healthy body weight [18] than those who skip breakfast. Regular consumption of a breakfast meal may reduce the risk of obesity and other chronic diseases [25]- [26]. Eating breakfast help to reduce dietary fat and minimize impulsive snacking promoting a preventive measure in obesity [27].…”
Section: Introductionmentioning
confidence: 99%
“…39 This association between breakfast skipping and higher body mass index (BMI) has been reported globally, primarily in cross-sectional studies. 33,[40][41][42][43][44][45][46][47][48][49][50][51] For example, in NHANES 1999 to 2002, young adults (n=5316; age, 20-39 years) who reported consuming ready-to-eat cereal were 31% less likely to be overweight/obese and 39% less likely to have abdominal obesity compared with breakfast skippers. 52 Additionally, a meta-analysis of 19 studies in the Asian and Pacific regions (n=19 108 participants) demonstrated a pooled odds ratio (OR) of 1.75 (95% confidence interval [CI], 1.57-195) for prevalence of overweight or obesity among the lowest compared with the highest breakfast consumption frequency.…”
mentioning
confidence: 99%